GREEN INTELLECTUAL CAPITAL AND ENVIRONMENTAL MANAGEMENT ACCOUNTING: A LITERATUR REVIEW - Niken Safitri; Nurmala Ahmar; Muhammad Zaky; Moh. Ali Rahmani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
In the last two decades, the